Physical and transcriptional map of an aflatoxin gene cluster in Aspergillus parasiticus and functional disruption of a gene involved early in the aflatoxin pathway. - Trail, F (1995)
Two genes involved in aflatoxin B1 (AFB1) biosynthesis in Aspergillus parasiticus, nor-1 and ver-1, were localized to a 35-kb region on one A. parasiticus chromosome and to the genomic DNA fragment carried on a single cosmid, NorA. A physical and transcriptional map of the 35-kb genomic DNA insert in cosmid NorA was prepared to help determine whether other genes located in the nor-1-ver-1 region were involved in aflatoxin synthesis. Northern (RNA) analysis performed on RNA isolated from A. parasiticus SU1 grown in aflatoxin-inducing medium localized 14 RNA transcripts encoded by this region. Eight of these transcripts, previously unidentified, showed a pattern of accumulation similar to that of nor-1 and ver-1, suggesting possible involvement in AFB1 synthesis. To directly test this hypothesis, gene-1, encoding one of the eight transcripts, was disrupted in A. parasiticus CS10, which accumulates the aflatoxin precursor versicolorin A, by insertion of plasmid pAPNVES4. Thin-layer chromatography revealed that gene-1 disruptant clones no longer accumulated versicolorin A. Southern hybridization analysis of these clones indicated that gene-1 had been disrupted by insertion of the disruption vector. These data confirmed that gene-1 is directly involved in AFB1 synthesis. The predicted amino acid sequence of two regions of gene-1 showed a high degree of identity and similarity with the beta-ketoacyl-synthase and acyltransferase functional domains of polyketide synthases, consistent with a proposed role for gene-1 in polyketide backbone synthesis.